Реконструювання історії як реконструювання «Я». Роль спогадів у процесі ідентифікації у пізній прозі Інгеборг Бахман - Мельник, Д. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the problem of recollections in the novel «Malina» and two stories of an Austrian authoress («Simultan» and «Three Ways to the Lake») and their significance for finding the identity. The recollection became for protagonists the way to reconstruct their own past and thereafter their identity. In the late work of Ingeborg Bachmann the recollections have ambivalent significance: on the one hand, the protagonists find the way to themselves, on the other hand, this insight will lead them to death.